Mercury in yellow perch (perca falvescens) from Lake St. Francis and nearby tributaries of the St. Lawrence River. - Larivière, Émilie C. (University of Ottawa (Canada), 2001)
Mercury accumulation in fish is a substantial problem in northern temperate regions. Highly variable levels of mercury have been measured in fish from the St. Lawrence River. Here, I used stable isotopes of carbon (delta13C) as tracers of energy source to distinguish food webs of Lake St. Francis (a section of the St. Lawrence River near Cornwall, Ontario) from those of surrounding tributaries and coastal wetlands. I investigated the role of stable isotopes of nitrogen (delta15N) as estimates of trophic position, and I compared mercury accumulation in yellow perch ( Perca flavescens) from Lake St. Francis and the tributaries and coastal wetlands nearby. Since wetlands and tributaries were thought to be the major sites of methylmercury production, I predicted that fish feeding in tributaries would be more contaminated with mercury than fish of the same size or trophic level that are deriving energy from Lake St. Francis. Several components of the food webs of Lake St. Francis and its tributaries and coastal wetlands were sampled for mercury and/or stable isotope analyses (dissolved inorganic carbon (DIC), particulate organic matter (POM), zooplankton, benthic invertebrates, and yellow perch). (Abstract shortened by UMI.)
Keywords: Biology, Ecology.